PENGARUH BENDUNG TERHADAP PROFIL MUKA AIR SUNGAI BATANG GADIS - Sudarmanto , (Prokons: Jurnal Teknik Sipil, 2014)
Placement of the weir in the river Batang Gadis will cause population anxiety in the village Pulungan which located upstream weir as far as 3 km, due to a weir can cause water surface profile of the river getting higher and ultimately to increase the pool of flooding in residential areas.Assuming modeling of river a uniform flow, river cross-section has a rectangular shape with width 50 m and 40 m, the roughness Manning 0.0025, the profile of water flow floods that occurred in 2 yaears, 25 years, and 100 years before and after the existing weir can be calculated by numerical integration methods.  From the calculation, the length of the water behind the weir is 1.4 km upstream towards the weir, which means that the depth of the water level rises to as far as 1.4 km and after that the depth of water before and after there the weir is same. Because the village Pulungan located 3 km to the upstream, the weir did not affect the increase in the flood waters in the village Pulungan. At 2 years flood discharge does not cause inundation in the village Pulungan, but the flood discharge 25 years and 100 years has led to inundation in the village Pulungan with the depth of each pool 0.971 m and 1.675 m. Keywords: uniform flow, numerical integration, inundation, flood discharge.